Quality of Life of Patients With Heart Failure at Teaching Hospitals in Erbil City - Berivan Star Hamad Ameen; Yousif Mohammed Gardi (Hawler Medical University, 2019)
Background and objectives: Heart Failure is a common and significant health problem, with an increasing incidence and a gloomy prognosis that is often accompanied by a negative impact on the length and quality of life of patients. This study aimed to assess quality of life among patients with heart failure in Erbil city and to find the association of quality of life domains (physical, level of independence and social relationship) with some socio-demographic data (age, gender, level of education, and marital status) Methods: A quantitative design / a descriptive cross-sectional study was conducted at Hawler and Rizgary Teaching Hospitals in Erbil city Kurdistan region. This study was carried out from November 17th 2014 to November 17th 2015 on non-probability (purposive) samples was selected among 140 heart failure patients who were admitted to coronary care unit and medical ward of both teaching hospitals. Their quality of life was measured by standardized questionnaire of world health organization with some modification. Results: The findings of the study indicated that most patients were Female and Illiterate, their mean age was 68.75. Moreover, significant associations exist between levels of education with physical ability, level of independence, social domains, and marital state with physical domain. Conclusion: The study concluded that the majority of the study sample had moderate level of quality of life while less than one-fourth of them had poor level.